[Chata nad morzem] / St. Rolicz. - Rolicz, Stanisław (1913-1997); Rolicz, Stanisław (1913-1997) ([nakładem własnym autora], 1947)
Przedstawia zniszczoną drewnianą chatę nad brzegiem morza, w nocy, w czasie burzy.